Genetic dissimilarity for resistance to Mononychellus tanajoa (bondar) (Acari, Tetranychidae) among domesticated and wild Manihot species - Verônica de Jesus Boaventura; Rudiney Ringenberg; Carlos Alberto da Silva Ledo (Acta Scientiarum. Agronomy, 2015)
The aim of this study was to evaluate the genetic dissimilarity among wild and domesticated species of Manihot for resistance to cassava green mite during the insect life cycle. Nine accessions of wild Manihot species, M. esculenta ssp. flabellifolia, M. esculenta ssp. peruviana, and M. carthaginensis ssp. glaziovii, and two clones of M. esculenta (Cigana Preta and Sacaí) were evaluated under laboratory conditions at 25 ± 1°C, 70 ± 10% RH, and a 12-h photophase. Daily observations during the mite life cycle stages (larva-adult) were recorded. The data were subjected to an analysis of variance, a Scott-Knott test (5%), and Singh criterion, cluster, and principal component analyses. The larval-adult period ranged from 5.53 to 7.01 days: the longest period was observed on an M. glaziovii accession (GLA-19-DF) and the shortest on an M. flabellifolia accession (FLA-025V). The UPGMA method allowed the division of the genotypes into six groups, with the greatest distance between the FLA-025V and GLA-19-DF accessions. The first two main components explained 77.50% of the total accumulated variation. The association of the longest cycle duration of M. tanajoa with the lowest larval-adult viability suggests that GLA-19-DF is less favorable to mite development compared to the other accessions. Significant variability among the genotypes was observed.